Determinants of students’ interest in learning quantitative techniques among undergraduates in Sri lanka - Suntharalingam, T.; Thayaparan, A. (University of Jaffna, 2018)
This study explored the factors affecting the interest of students in learning quantitative technique subjects among the faculty of business studies third and fourth-year students in Vavuniya Campus, Vavuniya, Sri Lanka. A sample of 150 students was selected from two batches which were studied quantitative techniques subjects namely business mathematics, business statistics, computer applications in management and management science applications in their course. The student interests in learning of these subjects are associated with three explanatory variables such as contributions of learning to the major subjects, completing a research work and participating internship programs and the data related to these aspects were collected during the academic year 2016/2017. A structured questionnaire was used to collect the data on students' interests in learning quantitative subjects and the specific factors which influence it in the campus. The collected data were analysed using Pearson correlation statistic and multiple regression analysis, and the correlation results showed that all three explanatory variables have positively correlated with the students' interest in learning and it is statistically significant at 1% of level. Results of multiple regression model revealed that all the above explanatory variables have positively effect on students’ interest in learning the quantitative techniques subjects and out of them, contributions to complete their research work has more significant in determining the interest on the subjects. This finding may help to the academic staffs who teach these subjects to prepare their session plan with various structural strategies which they can use to teach the students effectively to enhance their interest of learning these subjects in the study area.
Keywords: Quantitative techniques; Learning interest of students; Internship programs; Pearson correlation; Business mathematics